2005
DOI: 10.1080/10623320590933752
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and Ovarian Steroid Regulation of Angiotensin II Type 1 and Type 2 Receptor Expression in Ovine Uterine Artery Endothelium and Vascular Smooth Muscle

Abstract: Although pregnancy is clearly associated with refractoriness to infused angiotensin II (AII) in the uteroplacental unit, there is still dispute over the mechanism by which angiotensin type 1 and type 2 receptors (AT1R and AT2R) may mediate this response in the uterine artery. This is in large part due to incomplete knowledge of levels of AT1R and AT2R expression and function in uterine artery endothelium (UA Endo) in the nonpregnant (NP) and pregnant (P) states, combined with the disagreement on whether AII ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 66 publications
2
13
0
Order By: Relevance
“…These observations are consistent with specific uterine rather than systemic (OA and RA) regulation of other endo and vsm receptors (e.g., ER-α, ER-ÎČ, angiotensin II type-1, and ANP) we have studied [28][29][30]32,33] suggesting that local gravid endocrine changes regulate these receptors. There was one notable exception in that RAendo LEPR were modestly downregulated 1-fold similar to that observed for UAendo 1-fold when compared to luteal phase animals.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…These observations are consistent with specific uterine rather than systemic (OA and RA) regulation of other endo and vsm receptors (e.g., ER-α, ER-ÎČ, angiotensin II type-1, and ANP) we have studied [28][29][30]32,33] suggesting that local gravid endocrine changes regulate these receptors. There was one notable exception in that RAendo LEPR were modestly downregulated 1-fold similar to that observed for UAendo 1-fold when compared to luteal phase animals.…”
Section: Discussionsupporting
confidence: 66%
“…In addition, others have elucidated the role of leptin on the regulation of the LEPR, showing that 7 days of twice daily leptin administration reduced the LEPR mRNA expression at the level of the arcuate nucleus in obese (ob/ob) mice, which may be indicative of leptin regulation of its LEPR [53]. Using similar ex vivo preparations, we have reported that compared to luteal phase animals, the periovulatory follicular period is a dramatic period [20,45] where other receptors in UAendo such as ER-α, ER-ÎČ [30,32,34], angiotensin II type-1 [28,33], and atrial natriuretic peptide (ANP) [29] are elevated. Collectively, these data clearly suggest an important role of endogenous estrogen-mediated elevated LEPR in the preparation of the uterus for the increased UBF during periovulatory period.…”
Section: Discussionmentioning
confidence: 86%
“…This was verified histologically in random samples (24). It should be noted that AT 1R are expressed in ovine uterine artery endothelium, upregulated in pregnancy, and mediate endothelial PGI2 and NO synthesis in uterine arteries from pregnant sheep (6,31,52). Thus, leaving the endothelium intact would have complicated any assessment of VSM function.…”
Section: Methodsmentioning
confidence: 99%
“…The interrelationship between the RAS and ER is complex. Depending on the tissue, oestrogen has varyingly been reported to downregulate AT1 receptors, in rat pituitary and hypothalamus (Seltzer et al 1992, Kisley et al 1999 and dog kidney, myocardium, liver and adrenal (Owonikoko et al 2004;see also Fischer et al (2002), but to up-regulate them at other sites, including rat kidney (Baiardi et al 2005) and sheep uterine artery endothelium (Sullivan et al 2005). Consistent with RAS up-regulation by oestrogen, intensity of AT1 receptor staining is most intense in the periovulatory period in human fallopian tube and uterine epithelia (Saridogan et al 1996a,b) and the AT2 receptor is also high during the proliferative phase in human myometrium (Pucell et al 1987, Mancina et al 1996, as it is in the rat ovary (Pucell et al 1987, Mancina et al 1996.…”
Section: Angiotensin II Er and Growth Factorsmentioning
confidence: 99%